4-Benzyloxy-3-(2,4-dichlorophenyl)-1-oxaspiro[4.5]dec-3-en-2-one - Liang-zhong Xu; Qun-qun Su; Jin Huang; Shan-qi Sun (Acta Crystallographica Section E, 2009)
In the title compound, C22H20Cl2O3, the cyclohexyl ring adopts a chair conformation. The furanyl ring plane makes dihedral angles of 70.10 (2) and 86.12 (3)° with the 2,4-dichlorophenyl ring and aromatic ring of the benzyl group, respectively. The crystal structure features weak intermolecular C—H...O and C—H...Cl hydrogen bonds.